A new diamond find and primary diamond potential of the Chetlas uplift (Middle Timan) - Aleksandr M. Pystin; Yurii V. Glukhov; Aleksandr A. Bushenev (Записки Горного института, 2023)
In the previously poorly studied southeastern part of the Chetlas uplift in the Middle Timan, a new occurrence of diamond satellite minerals and a diamond grain were found in the modern channel sediments of the Uvuy River basin. In order to assess the prospects of the area under consideration for identification of diamondiferous objects of practical interest, a characteristic of chromium-bearing pyropes and chromospinelides as the main kimberlite of diamond satellite minerals are given and the diamond grain itself is described. The material for the research was 16 schlich samples, each with a volume of 8 to 15 l. The minerals were studied using optical and scanning electron microscopy, Raman spectroscopy, laser luminescence and X-ray diffraction (Debye – Sherrer method). It is shown that among the pyropes, most of which correspond in composition to minerals of the lherzolite paragenesis, there are varieties belonging to the dunite-harzburgite paragenesis, including those belonging to diamond phase stability regions. Among the studied chromospinelides, chrompicotites and aluminochromites similar in composition to those found in rocks such as lherzolites and harzburgites, as well as in kimberlites, were identified. A diamond grain found in one of the samples has the form of a flattened intergrowth with distinct octahedron faces, complicated by co-growth surfaces with other mineral grains that have not been preserved to date. The discovery of the diamond and the established signs the formation of aureoles of the diamond satellites minerals in the channel sediments of the studied area open up the prospects for discovering their primary sources here.